Analysis of The Competitiveness of Lampung Robusta Coffee Bean - Daniel Triantoro; Deddy Aprilani; May Roni (International Journal of Economics, Business and Innovation Research, 2025)
As one of the largest coffee producing countries in the world, Indonesia has the opportunity to become a coffee exporting country to the world. Indonesia's coffee exports have been ranked the world's top for Robusta coffee since 1984. 94% of Indonesia's coffee exports are Robusta coffee. Global coffee consumption, especially robusta coffee, continues to increase every year, reaching 166 million bags (per bag per 60 kilograms) in 2021 There are many robusta coffee producing areas in Indonesia, one of which is Lampung province. Each coffee producing area has its own characteristics that are different from other areas. This study aims to determine the competitiveness of Lampung Robusta coffee beans in the global market using Diamond Porter's theory analysis on a case study of one of Lampung's coffee exporters which is Surya Bumi Sentosa company and using the Revealed Comparative Advantage (RCA) analysis of Lampung's Robusta coffee commodity results. This study uses descriptive primary data from interviews to explain Diamond Porters theory and secondary data to calculate the RCA index. The results of qualitative research show that the Surya Bumi Sentosa company has a high level of productivity supported by supporting factors owned by the company so that it produces quality coffee beans that are able to compete abroad. The results of the RCA study show that the average value of the Lampung RCA index in 2019-2023 is 58.96. The RCA index value above 1 proves that Lampung has good competitiveness in the global market.